Studi Kasus Pemanfaatan AI dalam Pengembangan Bahan Ajar Literasi Berimbang oleh Mahasiswa Pendidikan Guru Sekolah Dasar - Amalia, Eva (Borobudur Educational Review, 2026)
The integration of AI in education opens opportunities for developing more creative, adaptive, and efficient teaching materials. This study aims to describe the perceptions, processes, and reflections of elementary school teacher education students regarding the use of Artificial Intelligence (AI) in developing balanced literacy teaching materials. Using a qualitative case study approach, the research involved 60 students enrolled in a Balanced Literacy course. Data were collected through semi-structured online questionnaires and analyzed thematically. The results indicate that students hold a positive perception of AI, as it accelerates and simplifies the design of instructional materials. In the development process, AI was utilized to determine themes, design literacy activities, and integrate text, images, and interactive media. However, student reflections revealed that their confidence in the ethical use of AI remains relatively limited. These findings suggest that while students recognize the functional benefits of AI in learning, ethical concerns—such as misuse, academic dishonesty, privacy, and transparency—remain high. Consequently, institutions may need to strengthen ethical guidelines, digital literacy education, and clear policies on responsible AI use to enhance student trust in its ethical implementation.